2021
DOI: 10.1002/aocs.12483
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Field Nuclear Magnetic Resonance Time Domain Characterization of Polyunsaturated Fatty AcidRich Linseed and Fish Oil Emulsions during Thermal Air Oxidation

Abstract: Linseed contains high levels of polyunsaturated fatty acids (PUFA), such as α‐linolenic acid (> 50% ALA‐18:3), that are naturally protected against thermal oxidation by their encapsulation within linseed oil bodies (OB) by multiple components including antioxidant proteins and mucilage emulsifying agents. Linseed OB emulsions (LSE) can be produced by grinding linseed seeds, adding water, adjusting pH, and sonication. This is a process that can encapsulate externally added PUFA to minimize their thermal oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…However, not all peroxidation reactions generate MDA, therefore TBA data may be misleading. GC-MS is another common methodology used in the assessment of PUFA's degree of oxidation, that requires a complex sample preparation characterized by lipid extraction and subsequent derivation steps, which are very time consuming [37].These and other spectroscopic methods such as HF 1 H NMR and FTIR are limited in the resolution they can achieve of the different chemical and morphological states of PUFA oils and emulsions [7,41]. Hwang [7] suggested the development of methods that combine the concomitant detection of multiple oxidation products for the consistent assessment of lipid oxidation.…”
Section: Comparison Of 1 H Lf Nmr With Common Methods Of Characterizi...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, not all peroxidation reactions generate MDA, therefore TBA data may be misleading. GC-MS is another common methodology used in the assessment of PUFA's degree of oxidation, that requires a complex sample preparation characterized by lipid extraction and subsequent derivation steps, which are very time consuming [37].These and other spectroscopic methods such as HF 1 H NMR and FTIR are limited in the resolution they can achieve of the different chemical and morphological states of PUFA oils and emulsions [7,41]. Hwang [7] suggested the development of methods that combine the concomitant detection of multiple oxidation products for the consistent assessment of lipid oxidation.…”
Section: Comparison Of 1 H Lf Nmr With Common Methods Of Characterizi...mentioning
confidence: 99%
“…Linseed O/W emulsions (LSEs) of the present study are made from linseed oleosomes (oil bodies, OB) as described in detail by Resende et al [41]. In Section 2.2 the structural organization of LSE vesicles was described as oil encapsulated on the inside by different interfacial components such as polar head groups of amphiphiles, with their hydrophobic tails within the vesicle's core isolated from the continuous aqueous matrix environment.…”
Section: Demonstration Of Td Sensor Fingerprint Mapping Of Food O/w E...mentioning
confidence: 99%
“…Based on these result, we speculate that in ovo injection of PUFA in the yolk sac will have great potential to influence the embryonic development and broilers performance. Meanwhile, the study shown that n-6 PUFA in soybean oil accounts for about 51% and n-3 PUFA is about 6.8% ( Messina et al, 2021 ), while the linseed oil contains α-linolenic acid, which belongs to one of the n-3 PUFAs, more than 50% ( Resende et al, 2021 ). Hence, this study was conducted to explore the effects of IOF and dietary supplement of soybean oil (rich in n-6 PUFA) or linseed oil (rich in n-3 PUFA) on performance and immune function of broilers from 19 d incubation to 21 d post-hatch.…”
Section: Introductionmentioning
confidence: 99%